“When things are equal all over the world the symbols can be the same”: Isotype in West Africa - Kindel, Eric (InfoDesign, 2022)
This is a study of work undertaken by the Isotype Institute in British colonial West Africa in the 1950s. It begins by reviewing the idea of "international", as set out by Otto Neurath, the inventor of Isotype. The discussion extends to initiatives whose aims included bringing Isotype work into contact with Africa and Africans, a possibility that greatly interested Neurath, but which he never realised. Projects later completed in West Africa by the Isotype Institute under its director, Marie Neurath, illustrate how Isotype’s international method, approach, and symbols were adapted in response to local conditions. An addendum situates the work of the Isotype Institute within a broader context of development in Britain's West African colonies after the Second World War.